Analysis of Physical Status Indicators of Primary School Students (Texas Journal of Multidisciplinary Studies, 2022)
This article analyzes the indicators of physical development and physical fitness of primary school students. Indicators of physical development and physical fitness of students were also developed by innovative methods.